Cx43 and AKAP95 regulate G1/S conversion by competitively binding to cyclin E1/E2 in lung cancer cells. Issue 6 (27th April 2020) - Chen, Renzhen; Chen, Yu; Yuan, Yangyang; Zou, Xuan; Sun, Qian; Lin, Hongyan; Chen, Xiaoyi; Liu, Mingda; Deng, Zifeng; Yao, Youliang; Guo, Dongbei; Zhang, Yongxing
Abstract: Background: This study aimed to overexpress or silence connexin 43 (Cx43) and A‐kinase anchoring protein 95 (AKAP95) in human A549 cells to explore their effects on cyclins and on G1/S conversion when the interrelationship of Cx43, AKAP95, and cyclin E1/E2 changes. Methods: The study mainly used Western blot analysis and Co‐immuno precipitation to detect the target protein in Cx43/AKAP95 over expressed human A549 cells, and the relationship of proteins Cx43, AKAP95 and Cyclin E during G1‐S phase was explored with qualitative and quantitative analysis. Results: The overexpression of Cx43 inhibited the expression of cyclin D1 and E1 by accelerating their degradation and reduced the Cdk2 activity that blocked the DNA transcription activity. However, the overexpression of AKAP95 increased the expression of cyclin D1 and E1 and inhibited their degradation, and enhanced the Cdk2 activity that promoted the DNA transcription activity. Cx43 and AKAP95 competitively bound to cyclin E1/E2, and the competitive binding affected the Cdk2 activity, Rb phosphorylation, DNA transcription activity, and G1/S conversion. Conclusions: This study showed that the expression of ERK1/2, PKA, and PKB increased when BEAS‐2B cells were treated with PDGF‐BB, suggesting that ERK1/2, PKA, and PKB might be involved in the binding of AKAP95 with cyclin E, or the separation of AKAP95 from Cx43 from cyclin E1/E2. The specific mechanism underlying this process still needs further exploration.